An investigation on the effects of resection angle on apical sea! - Razmi H; Yousefi A (Tehran University of Medical Sciences, 2003)
Statement of Problem: The goal of a successful endodontic surgery is to establish an adequate seal in apical region. Therefore during surgery, root-end resection is essential for an appropriate situation and proper access."nPurpose: The aim of this study was to determine the most appropriate root-end resection angle to establish adequate apical seal in periapical surgery,"nMaterials and Methods: Forty-five intact extracted human maxillary central incisors were randomly divided into three 15-tooth groups. The root canals were instrumented and then obturated using lateral condensation technique. AM roots were resected at 3mm from apical portion. Angles of root resection for each group were 0, 30 and 45 degrees. Then all teeth surfaces, except the cut ones, were covered with nail polish and immersed in methylen blue for 7 days. After 7 days, nail polish was removed from the surfaces and samples were split in buccolingual direction. Then, dye penetration (mm) was measured using a stereozoom microscope (Loupe) [X4 magnification] and eye lens. In order to analyze the data, unilateral variance analysis was used."nResults: The values of dye penetration were: 7.23±3.34 (0°), 8.46±3.01(30°) and 9.74±4.11 (45°). There"nwas no significant difference between three groups (P>0.05). Conclusion: It is suggested that the angle of root-end resection put a limited effect on apical seal if retrograde cavity depth is increased.